Interferons at the crossroad of cell death pathways during gastrointestinal inflammation and infection - Iris Stolzer; Barbara Ruder; Markus F. Neurath; Claudia Günther (Elsevier, 2021)
Interferons (IFNs) are pleiotropic immune-modulatory cytokines that are well known for their essential role in host defense against viruses, bacteria, and other pathogenic microorganisms. They can exert both, protective or destructive functions depending on the microorganism, the targeted tissue and the cellular context. Interferon signaling results in the induction of IFN-stimulated genes (ISGs) influencing different cellular pathways including direct anti-viral/anti-bacterial response, immune-modulation or cell death. Multiple pathways leading to host cell death have been described, and it is becoming clear that depending on the cellular context, IFN-induced cell death can be beneficial for both: host and pathogen. Accordingly, activation or repression of corresponding signaling mechanisms occurs during various types of infection but is also an important pathway for gastrointestinal inflammation and tissue damage. In this review, we summarize the role of interferons at the crossroad of various cell death pathways in the gut during inflammation and infection.